Pencucian Secara Kimia Membran Ultrafiltrasi Sistem Aliran Cross Flow Pada Proses Penyaringan Air Terproduksi - Anggi Dwi Saputra; Syarfi Syarfi; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Produced water is water that obtained from the process of oil mining. Based on the characteristic that the produced water is classified as to the wastewater, required treatment before being discharged into water bodies. One of the alternative technologies that can be used for produced water treatment is membrane technology. The main challenge in the use of membrane technology is fouling. This research aims to study the trans-membrane pressure on flux, study the effectiveness and efficiency of NaOH and detergent in the regeneration process of ultrafiltration membranes on operation filtration of produced water. The study was conducted using ultrafiltration membranes by feeding produced water. The method used is by varying the operating pressure of 0.5 bar and 1 bar, variations in the concentration of NaOH and Detergents 0.5%, 1% and 1,5%. Filtration process of produced water lasted for 120 minutes and each leaching time is 30 minutes, the highest effectiveness rate of 30.55% obtained by using detergent 1.5%, the highest leaching efficiency based on flux recovery value is 69.66% and 30.55% for removal resistance, the highest flux value after chemical leaching obtained 0.8950 ml/menit.cm2 in trans-membrane pressure of 0.6 bar and the concentration of the detergent 1.5%. Keywords: Cross flow; Detergen; NaOH; Produced water; Ultrafiltration.